Curcumin analog DK1 induces apoptosis in human osteosarcoma cells in vitro through mitochondria-dependent signaling pathway - Aziz, Muhammad Nazirul Mubin; Hussin, Yazmin; Che Rahim, Nurul Fattin; Nordin, Noraini; Mohamad, Nurul Elyani; Yeap, Swee Keong; Yong, Chean Yeah; Masarudin, Mas Jaffri; Cheah, Yoke Kqueen; Abu, Nadiah; Akhtar, Muhammad Nadeem; Mohammed Alitheen, Noorjahan Banu (M D P I AG, 2018)
Osteosarcoma is one of the primary malignant bone tumors that confer low survival rates for patients even with intensive regime treatments. Therefore, discovery of novel anti-osteosarcoma drugs derived from natural products that are not harmful to the normal cells remains crucial. Curcumin is one of the natural substances that have been extensively studied due to its anti-cancer properties and is pharmacologically safe considering its ubiquitous consumption for centuries. However, curcumin suffers from a poor circulating bioavailability, which has led to the development of a chemically synthesized curcuminoid analog, namely (Z)-3-hydroxy-1-(2-hydroxyphenyl)-3-phenylprop-2-en-1-one (DK1). In this study, the cytotoxic effects of the curcumin analog DK1 was investigated in both U-2OS and MG-63 osteosarcoma cell lines using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and cell death was microscopically examined via acridine orange/propidium iodide (AO/PI) double staining. Flow cytometer analysis including Annexin V/Fluorescein isothiocyanate (FITC), cell cycle analysis and JC-1 were adapted to determine the mode of cell death. Subsequently in order to determine the mechanism of cell death, quantitative polymerase chain reaction (qPCR) and proteome profiling was carried out to measure the expression of several apoptotic-related genes and proteins. Results indicated that DK1 induced U-2 OS and MG-63 morphological changes and substantially reduced cell numbers through induction of apoptosis. Several apoptotic genes and proteins were steadily expressed after treatment with DK1; including caspase 3, caspase 9, and BAX, which indicated that apoptosis occurred through a mitochondria-dependent signaling pathway. In conclusion, DK1 could be considered as a potential candidate for an anti-osteosarcoma drug in the near future, contingent upon its ability to induce apoptosis in osteosarcoma cell lines.